2015
DOI: 10.1371/journal.pone.0133072
|View full text |Cite
|
Sign up to set email alerts
|

Caveolin-1 Dependent Endocytosis Enhances the Chemosensitivity of HER-2 Positive Breast Cancer Cells to Trastuzumab Emtansine (T-DM1)

Abstract: The humanized monoclonal antibody-drug conjugate trastuzumab emtansine (T-DM1, Kadcyla) has been approved by the U.S. FDA to treat human epidermal growth factor receptor 2 (HER-2)-positive metastatic breast cancer. Despite its effectiveness in most patients, some are initially resistant or develop resistance. No biomarker of drug resistance to T-DM1 has been identified. Antibody-drug efficacy is associated with antibody internalization in the cell; therefore, cellular sensitivity of cells to the drug may be li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
44
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 56 publications
(70 reference statements)
5
44
0
Order By: Relevance
“…Unlike MMAF, monomethyl auristatin E (MMAE) does not exist as a charged molecule at neutral pH and is membrane permeable. Data herein implicate caveolae-mediated endocytosis in T-DM1 resistance; however, another group has suggested that caveolae-mediated endocytosis may sensitize cells to T-DM1 (33). Although these data implicate a possible role for CAV1, the inherent differences in sensitivity to free DM1 (18) may explain the differences in basal sensitivity to T-DM1 seen across the high HER2 cell lines evaluated in that study.…”
Section: Discussionmentioning
confidence: 53%
“…Unlike MMAF, monomethyl auristatin E (MMAE) does not exist as a charged molecule at neutral pH and is membrane permeable. Data herein implicate caveolae-mediated endocytosis in T-DM1 resistance; however, another group has suggested that caveolae-mediated endocytosis may sensitize cells to T-DM1 (33). Although these data implicate a possible role for CAV1, the inherent differences in sensitivity to free DM1 (18) may explain the differences in basal sensitivity to T-DM1 seen across the high HER2 cell lines evaluated in that study.…”
Section: Discussionmentioning
confidence: 53%
“…5A). Since it has been reported that Her2 can be taken up via caveolin-1 dependent endocytosis and, to a lesser extent, clathrin-mediated endocytosis, [59][60][61][62] this difference likely represents anti-Her2-scFv-exosomes binding to Her2 and concomitant internalisation with the receptor. Thus, by directing exosomes to bind to a specific cell surface receptor, we have shown that it is possible to alter the trafficking and likely intracellular fate of the cargo.…”
Section: Discussionmentioning
confidence: 99%
“…It is believed that the HER2/T-DM1 conjugate enters cancer cells via the clathrin-dependent endocytosis pathway. However, a clathrin-independent mechanism, such as caveolae membranes composed mainly by caveolin-1 has also been demonstrated (22). Furthermore, it has been shown that the high endocytic activity of stem cell-like breast cancer cells make them particularly sensitive to T-DM1 (23).…”
Section: Discussionmentioning
confidence: 99%